High temperature crystal chemistry of the n = 3 Ruddlesden-Popper phase LaSr3Fe1.5Co1.5O10 - δ - Prado, Fernando Daniel (2015)
The crystal chemistry of the n = 3 Ruddlesden-Popper phase LaSr3Co1.5Fe1.5O10 - δ has been studied in the temperature range 20 ≤ T ≤ 900 °C by in situ Neutron Powder Diffraction (NPD), and thermogravimetric and linear expansion measurements. The presence of oxygen vacancies at the O(2) and O(4) crystal sites, in the central perovskite layer, along with the variation of the bottleneck space available for oxygen migration with temperature at T > 300 °C indicates the O(4)-O(4) jumps predominate during oxide ion diffusion. Absolute oxygen content measurements support oxygen excess (> 10.0) at temperatures below 300 °C, which is unusual for the n = 3 R-P phases. The total expansion in the temperature range 25 ≤ T ≤ 900 °C, α = αV3 = 26.5 (1) × 10- 6 K- 1, is twice the values reported for the electrolytes. The linear expansion along the c-axis, αc = 34.15 (1) × 10- 6 K- 1, is mainly absorbed by the perovskite block while the width of the rock salt layers remains nearly constant. Additionally, the oxygen chemical expansivity (βC) value determined for this layered compound, βC = 0.670, was found to be approximately three times larger than those reported for the three dimensional perovskite system La1 - xSrxCoO3 - δ.